Experimental Investigation of LPG/H2/Air Premixed Flame Stability Zone - Mokhles Tawfeeq AbdulAmeer; Haroun A.K. Shahad; Samer Mohammed AbdulHaleem (Journal of Engineering and Technological Sciences, 2020)
Flame stability, environmental changes and fossil fuel shortage represent major challenges to any successful combustion device utilization. In this study, the stability zone of laminar premixed ILPG/ -air flames was investigated experimentally. Non-swirling burners with different diameters (10, 12.5, and 17 mm) were employed to characterize the ï¬‚ashback and blow-off limits. Different hydrogen blends (0%-50%) at equivalence ratios (ER) (0.6-1.4) were used. The results show that maximum ï¬‚ashback limits occurred at ER slightly richer than stoichiometric, with the mixture flow rate at a flashback of (3.75, 7.25 and 14) LPM for the 50% hydrogen blending ratio and a burner diameter of (10, 12.5 and 17 mm), respectively. When hydrogen blending was 50% at stoichiometric condition, the critical velocity gradient at flashback increased from (469.9-650.8 1/s) with 10 mm diameter, and the critical velocity gradient at blow-off increased from (1538-2936 1/s). It was observed that the ï¬‚ashback limits decreased with increasing burner diameter. Its limit increased with increasing hydrogen addition to the ILPG. The blow-off limit increased with increasing fuel concentration. This paper further presents the stability zone for ILPG/air combustion for a non-swirling burner with a 10-mm diameter and different hydrogen blends. It was found that the stability zone was narrow on the lean combustion side and enhanced with increasing diameter and hydrogen addition.